Galápagos land iguana (Conolophus subcristatus) as a seed disperser - Traveset, Anna (2016)
The role of the most common land iguana (Conolophus subcristatus) in the Galápagos Islands as an effective seed disperser is explored in this study. A total of 5705 seeds of 32 plant species were identified from 160 scats, 4545 of which (80%) appeared visually undamaged. Germination trials of 849 seeds from 29 species revealed that at least 10 species remained viable after passing through the iguana's gut, although only a small proportion of those seeds (4%) germinated. In any case, we argue that C. subcristatus exerts an important role on the 7 Galapagos islands where it occurs because of its abundance and capacity to ingest and disperse seeds at long distances. Our results strongly suggest that the Galápagos C. subcristatus plays an important role as a seed disperser of not only of native species but also some introduced plants in the Galápagos Islands.